The presidency of John F. Kennedy - Giglio, James N., 1939- (American presidency series., 2006)
"Like the first edition, this new edition provides a sharp and thoughtful analysis of both domestic and foreign affairs and underscores that, despite his undeniably brief tenure in office, the state of the nation actually did improve on Kennedy's watch. Featuring an expanded bibliographical essay and twenty-two photos from the JFK library, The Presidency of John F. Kennedy remains the definitive appraisal of Camelot's kingdom."--Jacket